The Growth Response of Propagules Rhizophora mucronata in Soaking Coconut Water and Applying NPK Fertilizer - Ratna Fitry Yenny; Zahratul Millah; Dewi Firnia; Hestina Tri Jayanti; Adi Susanto (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Rhizophora mucronata is a mangrove plant that has the strongest root system and often chosen in mangrove forest rehabilitation. Planting Rhizophora mucronata often fails due to limited seed supply and poor seedling quality. This study aims to determine the growth response of Rhizophora mucronata propagules to coconut water immersion and NPK fertilizer. The research was conducted from February 2023 to June 2023 at the screenhouse of the Banten Agricultural Instrument Standardization Implementation Center (BPSIP) Banten. The research was arranged in a Randomized Group Design with three replications and consisted of two factors. The first factor is soaking treatment consisting of 2 levels, namely soaking without coconut water and soaking with coconut water. The second factor is the concentration of NPK fertilizer consisting of 4 levels, namely 0 g/plant, 9 g/plant, 12 g/plant, and 15 g/plant. The parameters observed were shoot emergence time (days), leaf emergence time (days), stem diameter (mm), number of roots (strands), and root length (cm). The results showed that coconut water soaking treatment gave results that significantly affected to stem diameter, number of roots and root length. The application of NPK fertilizer 9 g/plant gives results that significantly affected to shoot rupture time, leaf emergence time, number of roots, and root length.